Properties and applications of ceramic sensors and actuations in smart city - Tan, Hou Zuo (2015)
This research study will be focusing on one of the most important and commonly used material, ceramics. It constitutes of the various roles that ceramic has played, its properties, last but not least the applications and properties of ceramic temperature sensor, humidity sensor and piezoelectric actuator. Being one of the earliest manmade materials ceramic consists of naturally-occurring raw material. It has been extensively researched due to its broad range of properties. In essence, it has been a preferred material by manufacturers or engineers in constructing or coating parts of sensor and actuator due to its wide range of properties. The invention of sensors and actuators make monitoring and controlling systems possible. These processes are crucial in constructing a smart city. A smart city emphasize on integrating technologies to benefit the standard of living of people's life. With the increasing demand for smart technologies, it is crucial to research on materials that are most suitable for making sensor and actuators. Ceramic has being employed due to its attractive range of properties such as good electrical conductivity, good heat resistance, good insulator and its dielectric properties. This paper includes the working principle of these sensors or actuators.